Piezoresponse force microscopy behaviour of Bi4Ti3O12 ceramics with various excess bismuth - Aguiar, Ederson Carlos [UNESP]; Simões, Alexandre Zirpoli [UNESP]; Moura, Francisco; Cilense, Mário [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (National Library of Serbia, 2011)
Bismuth titanate (Bi4 Ti3 O12 - BIT) ceramics derived from different amounts of excess Bi2 O3 were prepared using the polymeric precursor method. In spite of excess bismuth, single phase ceramics were obtained with a controlled microstructure. Raman analysis evidenced typical vibrational bands of the BIT phase. UV-vis spectra indicated that excess Bi2 O3 causes a reduction in defects in the BIT lattice due to the suppression of oxygen vacancies located at the octahedral BO6 – ion. The microstructure and electrical properties are strongly dependent on the excess Bi2 O3 . Appropriate initial Bi2 O3 excess reduces the leakage current and loss tangent and thereby improves the polarization of BIT ceramics. Rietveld analyses confirmed that the powders crystallize in an orthorhombic structure with a space group of Fmmm at room temperature. The polarization reversal was investigated by applying ac voltage through a conductive tip during the area scanning and was investigated by piezoresponse force microscopy (PFM).
Keywords: bismuth titanate; chemical synthesis; annealing; dielectric properties